PELATIHAN PENGOLAHAN BAYAM MERAH UNTUK PENCEGAHAN ANEMIA DAN STUNTING - Wida Ningsih; Afdhil Arel; Yahdian Rasyadi (Politeknik Negeri Sriwijaya, 2022)
Stunting is failure to thrive due to lack of nutritional intake that lasts for a long time from pregnancy to 24 months of age. Efforts to prevent stunting are carried out by meeting the nutritional needs of pregnant women, providing exclusive breastfeeding and eating complementary foods and maintaining environmental cleanliness. One of the nutrients during pregnancy that needs to be considered is the fulfillment of iron needs to prevent nutritional anemia caused by iron deficiency. Based on the results of a survey by a National Competent Institution, the Indonesian Nutritional Status Survey (SSGI), the Padang Panjang stunting rate was set at 20% and based on information from the Padang Panjang City Service Head from Posyandu cadre data, the Padang Panjang stunting rate reached 15.57%. Red spinach is a vegetable that contains a lot of iron that can be consumed as an alternative food to meet iron needs. Iron plays a role in the formation of hemoglobin. The purpose of this community service is to increase the knowledge of pregnant women and mothers with toddlers about the benefits of red spinach and how to process red spinach into noodles. The method used was counseling and distribution of noodles from red spinach for counseling participants. The outputs obtained in this activity are pregnant women and mothers with toddlers who know the benefits of red spinach, can process red spinach into noodles and are willing to consume red spinach as an effort to prevent anemia and stunting.